POSTMORTEM DIAGNOSIS OF ONE POPULATION OF BLUE-WINGED TEAL (Anas discors) IN THE STATE OF VERACRUZ - Lorena López-De-Buen; VÃctor Manuel DÃaz-Mérida; Bernardo A. López-Yáñez (Tropical and Subtropical Agroecosystems, 2011)
The health status of 30 Blue-winged Teal (Anas discors) hunted in Amatitlán, in the central region of the state of Veracruz, Mexico, was assessed. The ducks were weighed, the wings were morphometrically measured, and of each organ the appearance, weight and length were evaluated, making comparisons between males and females, and between adults and immatures. The males weighed more than the females (n = 30, F(1,28) = 9.525, P = 0.004) and the adults more than the immatures (n = 19, F(1,17) = 6.526, P = 0.020). In all the groups the length of the wings was similar, as well as the internal organs had normal color, texture and location. The weight and size of lungs (5.4 g, 441 mm), liver (8.8 g, 608 mm), pancreas (1.5 g, 572 mm), gizzard (20.03 g, 448 mm) and intestines (21 g) were also similar among groups; however, the heart (3.8 g, 290 mm) was larger in the males (n = 30, F(1,28) = 13.513, P = 0.0009), and the kidneys (3 g, 505 mm) were heavier in the immature males (n = 19, F(1,17) = 7.417, P = 0.014). It was concluded that the Blue-winged Teal were in good health when hunted.